Religious Values and Young People: Analysis of the Perception of Students from Secular and Religious Schools (Salesian Pedagogical Model) - Cívico Ariza, Andrea (Religions, 2020)
In a secularised and postmodernist social context, young people are increasingly distanced from religious beliefs. Nevertheless, in schools with a religious character, the main contents of the faith continue to be transmitted through the ideology and the pedagogical model. The objective of this study is to analyse the influence of the type of school on the perception of religious values. The “Adaptive Values Test” instrument was used on a sample of 456 students from secular and religious schools (Salesian) in the province of Seville during the 2018-2019 academic year. The consideration of religious values in Salesian students is also specifically analysed. The results obtained show that young people studying in schools with religious pedagogical models have a more positive view of faith than the students from secular schools. However, the rejection of the ecclesial institution occurs in students from secular schools and, to a lesser extent, in students from religious schools, becoming a common factor of distancing from religion. Young people studying in religious Salesian schools reflect significant gender differences in the perception of religious values. In these students, the exploratory factor analysis reflects three main factors, the key aspects of faith being valued more than the ecclesiastical hierarchy.